A Solution for Sustainable Utilization of Aquaculture Waste: A Comprehensive Review of Biofloc Technology and Aquamimicry - Nisar, Ubair; Peng, Daomin; Mu, Yongtong; Sun, Yu (Frontiers in Nutrition, 2022)
Biofloc technology (BFT) is gaining traction as a strategic aquaculture tool for boosting feed conversions, biosecurity, and waste-water recycling. The significant aspect of BFT is aquaculture with highest stocking density and minimal water exchange. It not only improves the system's water quality by removing inorganic nitrogen from wastewater but also serve as a suitable feed supplement and a probiotic source for cultured species. This technology is commonly used for shrimp and tilapia culture and can be used for both semi-intensive and intensive culture systems. Biofloc when combined with formulated diets forms a balanced food chain that improves growth performance. The nutrients in this system are continuously recycled and reused and forms an efficient alternative system in aquaculture. In addition to the reduction of water exchange, it is also considered as a bio-security measure since it prevents entry of disease from outside sources .Aquamimicry, a revolutionary concept that simulates natural estuarine conditions by developing copepods and act as a supplementary nutrition especially for shrimp culture. The review highlights the process, significance and developments of BFT, its microbial interactions, nutritional value, the transition from biofloc to copefloc and concept of aquamimicry to sustainably improve aquaculture production.